2007
DOI: 10.1038/sj.mp.4001948
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of lipid metabolism and gene expression in rat adipocytes during chronic olanzapine treatment

Abstract: Although antipsychotics are established drugs in schizophrenia treatment, they are admittedly known to induce side effects favoring the onset of obesity and worsening its complications. Despite potential involvement of histamine receptor antagonism, or of other neurotransmitter systems, the mechanism by which antipsychotic drugs increase body weight is not elucidated. The aim of the present study was to investigate whether chronic antipsychotic treatments can directly alter the regulation of two main functions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
59
3
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(78 citation statements)
references
References 41 publications
13
59
3
3
Order By: Relevance
“…Lipolytic activity was assessed by the glycerol released by fat cells into the medium after a 90-min incubation in 400 μl final volume with the tested agents, as previously described (19). Results were expressed as μmoles of glycerol released / 100 mg cellular lipids / 90 min, or as the percentage of 5 nM isoprenaline-induced stimulation.…”
Section: Chemicalsmentioning
confidence: 99%
“…Lipolytic activity was assessed by the glycerol released by fat cells into the medium after a 90-min incubation in 400 μl final volume with the tested agents, as previously described (19). Results were expressed as μmoles of glycerol released / 100 mg cellular lipids / 90 min, or as the percentage of 5 nM isoprenaline-induced stimulation.…”
Section: Chemicalsmentioning
confidence: 99%
“…12 A recent study, in which olanzapine, ziprasidone and haloperidol were tested on animal adipocytes, showed that only olanzapine administration decreased lipolysis in adipocytes, as well as induced a gene fatty acid synthase overexpression and a gene hormonesensitive lipase repression that resulted in a significant fat accumulation in rats. 13 In light of these considerations, it could be concluded that obesity event associated with administration of different APDs could be enhanced by several pathways. To our knowledge, no study has been performed to test different classes of atypical neuroleptics on human adipocytes.…”
Section: Introductionmentioning
confidence: 99%
“…Page 4 of 34 A c c e p t e d M a n u s c r i p t 4 drugs altered lipogenesis and lipolysis in favor of progressive lipid accumulation and adipocyte enlargement (Vestri et al, 2007;Minet-Ringuet et al, 2007). Studies on glucose transport into isolated rat epitrochlearis skeletal muscle did not evidence any effect of clozapine (Houseknecht et al, 2007).…”
Section: Introductionmentioning
confidence: 99%